Quality of Life and 1-Year Survival in Patients With Early Septic Shock: Long-Term Follow-Up of the Australasian Resuscitation in Sepsis Evaluation Trial. Issue 6 (June 2019) - Higgins, Alisa M.; Peake, Sandra L.; Bellomo, Rinaldo; Cooper, D. Jamie; Delaney, Anthony; Harris, Anthony H.; Howe, Belinda D.; Nichol, Alistair D.; Webb, Steve A.; Williams, Patricia J.
Abstract : Objectives: To examine long-term survival and quality of life of patients with early septic shock. Design: Prospective, randomized, parallel-group trial. Setting: Fifty-one hospitals in Australia, New Zealand, Finland, Hong Kong, and the Republic of Ireland. Patients: One-thousand five-hundred ninety-one patients who presented to the emergency department with early septic shock between October 2008 and April 2014, and were enrolled in the Australasian Resuscitation in Sepsis Evaluation trial. Interventions: Early goal-directed therapy versus usual care. Measurements and Main Results: Long-term survival was measured up to 12 months postrandomization. Health-related quality of life was measured using the EuroQoL-5D-3L, Short Form 36 and Assessment of Quality of Life 4D at baseline, and at 6 and 12 months following randomization. Mortality data were available for 1, 548 patients (97.3%) and 1, 515 patients (95.2%) at 6 and 12 months, respectively. Health-related quality of life data were available for 85.1% of survivors at 12 months. There were no significant differences in mortality between groups at either 6 months (early goal-directed therapy 21.8% vs usual care 22.6%; p = 0.70) or 12 months (early goal-directed therapy 26.4% vs usual care 27.9%; p = 0.50). There were no group differences in health-related quality of life at either 6 or 12 months (EuroQoL-5D-3L utility scores at 12 mo early goal-directed therapy 0.65 ± 0.33 vs usual care 0.64 ± 0.34; p = 0.50), with the health-related quality of life of both groups being significantly lower than population norms. Conclusions: In patients presenting to the emergency department with early septic shock, early goal-directed therapy compared with usual care did not reduce mortality nor improve health-related quality of life at either 6 or 12 months. Abstract : Supplemental Digital Content is available in the text.